Direct Radiative Forcing Induced by Light‐Absorbing Aerosols in Different Climate Regions Over East Asia. Issue 14 (9th July 2020) - Zhang, Xiaorui; Chen, Siyu; Kang, Litai; Yuan, Tiangang; Luo, Yuan; Alam, Khan; Li, Jixiang; He, Yongli; Bi, Hongru; Zhao, Dan
Abstract: Light‐absorbing aerosols (LAAs), mainly composed of black carbon (BC) and dust aerosols, are responsible for significant climate forcing through their strong absorption of solar radiation. A fully coupled meteorology‐chemistry model (WRF‐Chem) associated with satellite retrievals and in situ measurements is used to investigate the direct radiative forcing (DRF) induced by LAAs in different climate regions over East Asia. Results show that the annual all‐sky dust and BC DRF are −0.84 and 1.06 W m −2 at the top of atmosphere (TOA), −1.23 and −1.55 W m −2 at the surface (SUR), and 0.39 and 2.61 W m −2 within the atmosphere (ATM) over East Asia. Large LAAs DRF can be found in hyper‐arid, subhumid, and humid regions at the SUR and ATM where dust DRF dominates the surface cooling effect, while BC DRF is predominant in the eminent warming effect on ATM in most climate regions. The meteorological conditions in hyper‐arid region are associated with enhanced surface wind and weakened atmospheric wind, which is in favor of the emission and accumulation of dust supporting the positive LAAs DRF anomalies higher than 10 W m −2 in hyper‐arid region. The positive geopotential height anomalies over Northeast China weaken the westerly winds, which is beneficial to the accumulation of LAAs, and results in the positive LAAs DRF anomalies of 3 W m −2 in semiarid regions. The large LAAs mass loading, strong aerosol absorptive ability, and decreased cloudiness caused by northerly anomalies are responsible for the high LAAs DRF in humid region. Key Points: The distributions of light‐absorbing aerosols have large difference in different climate regions Dust is the main contributor to surface cooling while BC dominates atmospheric warming The meteorological conditions have impacts on the high radiative forcing in different climate over East Asia